Variation in wood density across South American tropical forests - Sullivan, Martin J. P.; Phillips, Oliver L.; Galbraith, David; Almeida, Everton; de Oliveira; Edmar Almeida; Almeida, Jarcilene; Dávila, Esteban Álvarez; Alves, Luciana F.; Andrade, Ana; Aragão, Luiz; Araujo-Murakami, Alejandro; et al. (Springer Science and Business Media LLC, 2026)
Wood density is a critical control on tree biomass, so poor understanding of its spatial variation can lead to large and systematic errors in forest biomass estimates and carbon maps. The need to understand how and why wood density varies is especially critical in tropical America where forests have exceptional species diversity and spatial turnover in composition. As tree identity and forest composition are challenging to estimate remotely, ground surveys are essential to know the wood density of trees, whether measured directly or inferred from their identity. Here, we assemble an extensive dataset of variation in wood density across the most forested and tree-diverse continent, examine how it relates to spatial and environmental variables, and use these relationships to predict spatial variation in wood density over tropical and sub-tropical South America. Our analysis refines previously identified east-west Amazon gradients in wood density, improves them by revealing fine-scale variation, and extends predictions into Andean, dry, and Atlantic forests. The results halve biomass prediction errors compared to a naive scenario with no knowledge of spatial variation in wood density. Our findings will help improve remote sensing-based estimates of aboveground biomass carbon stocks across tropical South America.